Intracardiac Mass as Initial Cardiac Manifestation of Behçet's Disease: Think before You Cut. Issue 8 (13th June 2014) - Leibowitz, David; Korem, Maya; Livovsky, Dan M.; Peleg, Hagit; Chajek‐Shaul, Tova; Hiller, Nurith
Mini‐Abstract Behçet's disease (BD) is a chronic multisystemic inflammatory disorder. Cardiac abnormalities including intracardiac thrombi have been described in up to 16% of cases. The clinical presentation of cardiac complications in BD may include fever, dyspnea, chest pain, hemoptysis, and edema. As intracardiac masses may be the presenting manifestation of BD, it is crucial for echocardiographers to consider BD in the differential diagnosis. A careful history and physical exam looking for signs and symptoms of BD is critical before considering surgical excision of unexplained intracardiac masses. If the final diagnosis is BD anti‐inflammatory therapy should be considered the basis of treatment.